2018
DOI: 10.1038/s41388-018-0333-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of maternal embryonic leucine zipper kinase with OTSSP167 displays potent anti-leukemic effects in chronic lymphocytic leukemia

Abstract: TP53 pathway defects contributed to therapy resistance and adverse clinical outcome in chronic lymphocytic leukemia (CLL), which represents an unmet clinical need with few therapeutic options. Maternal embryonic leucine zipper kinase (MELK) is a novel oncogene, which plays crucial roles in mitotic progression and stem cell maintenance. OTSSP167, an orally administrated inhibitor targeting MELK, is currently in a phase I/II clinical trial in patients with advanced breast cancer and acute myeloid leukemia. Yet, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
73
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 67 publications
3
73
2
1
Order By: Relevance
“…In contrast, MELK silencing was found to contribute to the delay of S phase progression by Beke et al andKig et al 13,30 Our study revealed that MELK may act as a negative regulator of the G1/S transition, which was consistent with Beke et al andKig et al To investigate the reason that MELK plays a different role in cell cycle progression according to previous studies, cell cycle assays of other cancer cell lines, such as liver cancer and kidney cancer, were assessed following MELK being knocked down. Moreover, MELK has been shown in some studies to promote tumorigenesis via the p53 pathway 13,23,25,[30][31][32]. Owing to the lack of additional tumour cell lines, we could not conclude that p53 affects the role of MELK in the cell cycle.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…In contrast, MELK silencing was found to contribute to the delay of S phase progression by Beke et al andKig et al 13,30 Our study revealed that MELK may act as a negative regulator of the G1/S transition, which was consistent with Beke et al andKig et al To investigate the reason that MELK plays a different role in cell cycle progression according to previous studies, cell cycle assays of other cancer cell lines, such as liver cancer and kidney cancer, were assessed following MELK being knocked down. Moreover, MELK has been shown in some studies to promote tumorigenesis via the p53 pathway 13,23,25,[30][31][32]. Owing to the lack of additional tumour cell lines, we could not conclude that p53 affects the role of MELK in the cell cycle.…”
mentioning
confidence: 83%
“…[6][7][8] MELK was associated with mitotic progression and DNA damage. 23 High levels of MELK are correlated with clinically aggressive disease and poor survival. 23 High levels of MELK are correlated with clinically aggressive disease and poor survival.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations